[(para‐Cymene)Ru(dppp)Cl][PF6]‐Catalysed Stereospecific Synthesis of O‐Dienyl Esters, and Evaluation of the Anticancer Activity of a Long‐Chain Fatty Acid O‐Dienyl Ester. Issue 11 (23rd March 2017) - Jena, Rajesh K.; Rajesh, Y.; Mandal, Mahitosh; Bhattacharjee, Manish
Abstract : O ‐Dienyl esters are obtained through the regio‐ and stereospecific addition of both aromatic and aliphatic carboxylic acids to terminal propargylic alcohols, with the sequential formation of a carbon–oxygen bond and dehydration, in the presence of [( p ‐cymene)Ru(dppp)Cl][PF6 ] (1 ). Also, the cytotoxicity and anticancer activity of the newly synthesized O ‐dienyl ester ( Z )‐3‐methylbuta‐1, 3‐dienyl oleate have been investigated. Abstract : Z ‐Configured O ‐dienyl esters have been obtained through the reaction of propargylic alcohols with carboxylic acids, including fatty acids, catalysed by [(η 6 ‐ p ‐cymene)Ru(η 2 ‐dppp)Cl] + . The anticancer activity of one of the fatty acid dienyl esters has been investigated.